Functional expression of plant sesquitepene synthases for isoprenoid production in lactococcus lactis - Song, Adelene Ai Lian (2012)
Plants produce a large variety of isoprenoids as secondary metabolites through the mevalonate (MVA) pathway and the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway. These isoprenoids have appealing characteristics such as flavour, fragrance,and therapeutic properties. However, since plants have many limitations in producing high yields of isoprenoids, systems such as Escherichia coli and Saccharomyces cerevisiae have been engineered as heterologous hosts to produce plant isoprenoids. Lactococcus lactis, a food grade homofermentative bacterium, is another potential heterologous cell factory for plant isoprenoids. Interestingly, L. lactis uses the MVA pathway more commonly found in eukaryotes for isoprenoid production. In this study, two different plant sesquiterpene synthases from Vanda Mimi Palmer (VMP) and Polygonum minus, respectively, were cloned and expressed in L. lactis. VMP is a highly scented tropical orchid hybrid of Vanda tesselata and Vanda Tan Chay Yan while P. minus is a highly fragranced local herbaceous plant commonly used for cooking in local delicacies. Four plasmid constructs denoted pNZ:VMPSTS,pNZ:VMPSTS:mvaA, pNZ:PMSTS and pNZ:PMSTS:mvaA were developed in this study. The sesquiterpene synthases from both plants were expressed optimally at 40 ng/ml nisin, 2 h post-induction. The recombinant proteins were purified and its function identified through in vitro enzymatic assays followed by GC-MS analysis. The VMP sesquiterpene synthase was found to produce multiple sesquiterpene products with germacrene D dominating its profile while the sesquiterpene synthase from P. minus was identified to be a B-sesquiphellandrene synthase. However, only the recombinant L. lactis expressing the P. minus B-sesquiphellandrene synthase was able to produce B-sesquiphellandrene in vivo. Using this recombinant L. lactis strain,an attempt to increase B-sesquiphellandrene production by overexpressing the HMGCoA reductase (HMGR), an established rate-limiting enzyme in the eukaryotic MVA pathway, was conducted. However, this effort was shown to increase the production of B-sesquiphellandrene only by 1.25-1.60 folds. Therefore, the MVA pathway’s transcriptomic profiles of the wild-type L. lactis and the various recombinant L.lactis constructed in this study were compared in hope of gaining some insights on the prokaryotic MVA pathway and future metabolic engineering strategies which may be feasible for the optimisation of plant isoprenoid production in L. lactis. Transcriptomic analysis revealed that HMGR may not be the rate-limiting enzyme in the prokaryotic MVA pathway and instead mvk encoding MVA kinase may be a better metabolic engineering gene target for increased isoprenoid production. Also, the genes mvaD and fni encoding diphosphomevalonate decarboxylase and isopentenyl pyrophosphate isomerase, respectively, may be important genes involved with the ability of the lactococcal host to produce heterologous isoprenoids in vivo. In conclusion, apart from demonstrating L. lactis as an alternative host for plant isoprenoid production, this study is the first study involving metabolic engineering of the prokaryotic MVA pathway for increased isoprenoid production and also provides important information on the potential bottle-necks in the lactococcal MVA pathway.